Об одном подходе к поиску функциональных зависимостей данных в реляционных системах - Филатов, В. А.; Доскаленко, С. Н. (ХНУРЕ, 2018)
The approach is suggested to identify previously unknown functional dependencies which are based on the analysis of a set of relational database data. The first step is to get a set of functional dependencies for each relationship. The similar operation for the universal relation of the target database is performed at the second step. At this step, functional dependencies among the attributes of different relationships, that is the interrelationships among the data that were established during the information system operation, can be identified. The method for determining their information novelty is suggested; this method consists in verifying the membership of the functional dependencies of the universal relation while discovering the union of sets of dependencies of individual relations. A promising direction for further research is the development of methods to implement the technology for verifying if the obtained dependencies correspond to the logical model of the domain.
The Approach to Searching for Functional Dependences of Data in Relational Systems
Keywords: relational database; functional dependence; universal relation; reengineering